Creativity in Citizen Cyberscience (Human Computation, 2016)
In the context of citizen cyberscience, creativity is generally thought to be positive and should be encouraged. When volunteers think “outside of the box” they bring their own unique perspectives to scientific problems and generate new ideas. In some cases, creativity can even lead to new scientific discoveries. However there are still many unanswered questions about creativity. Is creativity in citizen science just about scientific discovery, or are there other kinds of creative products in citizen cyberscience? How does creativity compare across different kinds of citizen cyberscience, such as volunteer thinking and participatory sensing? In Citizen Cyberlab we explored creativity across four different pilot projects: GeoTag-X, Virtual Atom Smasher, Synthetic Biology, and Extreme Citzien Science. We conducted 96 interviews in total: 86 with volunteers (citizen scientists) and 10 with scientists. Based on our findings, we present several creative products that are a result of active involvement in citizen cyberscience: discussing ideas, suggesting improvements, development of new technologies, gamification, artwork, creative writing, outreach activities, and the development of new research projects. We also discuss factors that encourage creativity, such as having a supportive environment for volunteers and building a sense of community.
Keywords: Citizen Science; Creativity; Cyberlab